2022
DOI: 10.1186/s13019-022-02050-y
|View full text |Cite
|
Sign up to set email alerts
|

Pleural effusions are associated with adverse outcomes after cardiac surgery: a propensity-matched analysis

Abstract: Background Pleural effusions commonly occur in patients recovering from cardiac surgery; however, the impact on outcomes is not well characterized. The purpose of this study is to characterize the clinical outcomes of cardiac surgery patients with pleural effusion. Methods All patients undergoing cardiac surgery between 2006 and 2019 at a tertiary care university hospital were included in this observational, cross-sectional analysis using propensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…Compared to patients without PE, those who developed PE after cardiac surgery and needed secondary drainage had a significantly longer hospital stay and a higher mortality rate. PE has been associated with worse outcomes after cardiac surgery [ 7 ]. In a single-center cohort study, TD after LVAD implantation was related to prolonged length of stay [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to patients without PE, those who developed PE after cardiac surgery and needed secondary drainage had a significantly longer hospital stay and a higher mortality rate. PE has been associated with worse outcomes after cardiac surgery [ 7 ]. In a single-center cohort study, TD after LVAD implantation was related to prolonged length of stay [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The lack of statistical significance may be attributed to the small sample size. Previous studies have shown that the duration of mechanical intubation is significantly longer in patients with PE after cardiac surgery, suggesting that TD might help reduce the duration of mechanical intubation [ 7 ]. Patients experienced a decrease in symptoms and increased walking distance 1 month postoperatively when TD was performed [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Post-surgical pleural effusion is the accumulation of fluid in the pleura after surgery. Pleural effusion can occur in 41 to 89% of patients undergoing procedures such as CABG especially in the first 7 days after surgery [8]. Accumulation of excess fluid can occur if excessive production, decreased absorption, or both exceed normal homeostatic mechanisms.…”
Section: Pleural Effusionmentioning
confidence: 99%
“…In the postsurgical period, there may be disturbances in hydrostatic pressure and homeostasis resulting in pleural effusion. The most common type of pleural effusion is transudate [7,8,9].…”
Section: Pleural Effusionmentioning
confidence: 99%
“…The deleterious effects of these underlying conditions are compounded by the sequelae of cardiac and thoracic surgery. Postoperative pulmonary edema, pleural effusions, and impaired respiratory mechanics including reduced functional residual capacity (FRC), decreased lung compliance and impaired cough may all be exacerbated by residual neuromuscular block [60,61].…”
Section: Cardiac and Thoracic Surgery Populationmentioning
confidence: 99%